3*3*3+8*(-2-3x)=-5*(2+x)-(x+15)

Simple and best practice solution for 3*3*3+8*(-2-3x)=-5*(2+x)-(x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*3*3+8*(-2-3x)=-5*(2+x)-(x+15) equation:


Simplifying
3 * 3 * 3 + 8(-2 + -3x) = -5(2 + x) + -1(x + 15)

Multiply 3 * 3
9 * 3 + 8(-2 + -3x) = -5(2 + x) + -1(x + 15)

Multiply 9 * 3
27 + 8(-2 + -3x) = -5(2 + x) + -1(x + 15)
27 + (-2 * 8 + -3x * 8) = -5(2 + x) + -1(x + 15)
27 + (-16 + -24x) = -5(2 + x) + -1(x + 15)

Combine like terms: 27 + -16 = 11
11 + -24x = -5(2 + x) + -1(x + 15)
11 + -24x = (2 * -5 + x * -5) + -1(x + 15)
11 + -24x = (-10 + -5x) + -1(x + 15)

Reorder the terms:
11 + -24x = -10 + -5x + -1(15 + x)
11 + -24x = -10 + -5x + (15 * -1 + x * -1)
11 + -24x = -10 + -5x + (-15 + -1x)

Reorder the terms:
11 + -24x = -10 + -15 + -5x + -1x

Combine like terms: -10 + -15 = -25
11 + -24x = -25 + -5x + -1x

Combine like terms: -5x + -1x = -6x
11 + -24x = -25 + -6x

Solving
11 + -24x = -25 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
11 + -24x + 6x = -25 + -6x + 6x

Combine like terms: -24x + 6x = -18x
11 + -18x = -25 + -6x + 6x

Combine like terms: -6x + 6x = 0
11 + -18x = -25 + 0
11 + -18x = -25

Add '-11' to each side of the equation.
11 + -11 + -18x = -25 + -11

Combine like terms: 11 + -11 = 0
0 + -18x = -25 + -11
-18x = -25 + -11

Combine like terms: -25 + -11 = -36
-18x = -36

Divide each side by '-18'.
x = 2

Simplifying
x = 2

See similar equations:

| (2b-5c)a= | | 9f-(3+2f)=-10 | | 2a-2+4a-8-a=-20 | | -7n=-9n-6 | | 6x-2-3x=x+6+x | | 1/8x-3/8x=2 | | x+2+6=-9 | | -4x-10=14 | | 3.5+10m=732 | | 6y=x^2-6 | | -6(-2x-8)=24 | | 3a/4a | | 1-(2-(3-x))=4x-(6+x) | | 35+1000m=732 | | -2y-5y-17=25 | | 5=1+7p-3p | | -2y-5y-17= | | 8+3(x-4)=-19 | | 4x^2/3x | | n+10+1+2n= | | 4/3=5/6-5 | | 4=6(3-2x)-14 | | 5(2m-4)=6(m-4) | | 8x+1=-1x-1 | | 2x+4y=2(x-3) | | y=4x^2-8x-3+10 | | 4Vx+16=2x+2 | | 5+5x+4x= | | 8=2(x-3)-4 | | -1(5d+1)=2(3d+3) | | 5x(5x+8)=-16 | | 18-3u+2u= |

Equations solver categories